Faktor Sosial Yang Mempengaruhi Interaksi Anak dan Perilaku Anak di Kelas - Maria Regina Jaga; Aplonia Nelci Ke Lomi; Priscilla Maria Assis Hornay (Jurnal Pendidikan Anak Usia Dini Undiksha, 2023)
Social factors show complex interactions and can affect children's social interactions. This research analyzes social factors that influence children's interactions and behavior in the classroom environment. This type of research is qualitative research. This qualitative research involved children and two of their teachers in kindergarten. Data collection methods use observation and interviews. The data collection instrument uses a questionnaire sheet. The data analysis technique uses qualitative descriptive analysis. Data were analyzed using content analysis techniques. The results show that respectful relationships, honest conversation and communication, intellectual engagement of students, shared ownership and responsibility in learning, and a classroom environment are the keys to effective learning for children. Teachers recognize children's progress, so they begin to value many of the social behaviors that children want to master. The classroom setting is an excellent place for children, and teachers pay attention to children's independent ability for tasks or skills through their interactions.